Hubungan Pengambilan Keputusan Kepala Sekolah dengan Motivasi Kerja Guru di SMA Swasta Sinar Husni - Purnama, Ayyu; Mesiono, Mesiono (MODELING: Jurnal Program Studi PGMI, 2024)
Teacher success is closely related to school success. A good school principal can influence and encourage teachers to actively participate in all school activities so that the school can achieve its vision and mission. This can be achieved by involving teachers more frequently in school decision-making processes. This quantitative research uses the correlation method. The goal is to create and use mathematical models, theories, and hypotheses about natural phenomena. The results of this research show that the principal's decision making variable and the teacher's work motivation variable at Sinar Husni Private High School have a significant correlation. The research results show that the Fcount value is greater than Ftable (41.914 is greater than 4.28) and the significance level is 0.00 greater than 0.05.